Integration Mobile Technology into English Lessons: A case study at VNU-ULIS and VNU-UED - Yen, Nguyen Thi Linh; Cuong, Ton Quang (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4148, 2018)
The purpose of this study is to investigate the mobile tools (based on Web 2.0 platform) for language activities in English lessons for non-linguistics students as well for linguistics specialized group of the two universities. While the first group is only introduced of English basic lessons with many language barriers, the second group of English linguistics students is attending to study linguistic phenomena. The study involved 21 newly enrolled Master degree students in Teaching Learning Methodology program (VNU-UED) participating in an introduction program of the English for educational purposes, and 25 linguistics specialized 4-th year students from VNU-ULIS.  The participants were allowed to use their own devices (smartphone, Ipad, Tablet, Laptop) during English lessons, as well as introduced mobile applications based on Web 2.0 platform for all their activities in and after the class (speaking, writing, reading, listening, translating and homework doing). The participants were interviewed about their effectiveness of using mobile phones as well as recorded in a number of activities inside and outside the classroom to compare their language evolvement, perception and development. In addition, surveys, recording, logging of weekly mobile activities and observations were performed.  The study results indicate that focusing English linguistic training with a mobile technology is useful and fun for both groups in term of developing language skills, as well as technology competencies which can lead to improved integration. Using a BYOD/BYOTs both inside and outside the classroom the participants expressed their need, interest and self-confidence in having more mobile apps for English learning despite of having linguistics background or not.